Photodegradation of Diclofenac in Aqueous Solution using Visible Light driven TiO2/g-C3N4 - JOHN JAYABALAN, PRASENNA (2021)
Emerging contaminants such as diclofenac is frequently detected in wastewater treatment plants because they are not specifically designed for pharmaceutical removal, which results in poor removal efficiency. Even though photocatalysis has emerged as a promising alternative, most of the reported photocatalyst are UV light driven, portrays fast recombination rate of electron-hole pair and has slow electron mobility. In order to overcome these shortcomings, in the present work, visible light-driven TiO2/g-C3N4 photocatalyst was synthesized for the photodegradation of diclofenac in aqueous solution. The morphological and optical properties of the photocatalyst were analyzed in which the formation of rutile phase TiO2 and improved band gap energy (3.18eV to 2.81eV) was clearly observed. The photodegradation efficiency was improved even at low catalyst loading (0.3g) within a period of 90 minutes, indicating the Z-scheme photocatalyst, successfully overcame the electron-hole pair's fast recombination rate. The photodegradation efficiency was represented as a function of all independent variables (irradiation time, initial solution pH, initial diclofenac concentration and catalyst loading), using a second-order quadratic model. Response surface methodology (RSM) was used to optimize the degradation process. A maximum degradation efficiency (93.49%) was achieved at the optimum conditions (irradiation time = 90min, initial solution pH = 5, initial diclofenac concentration = 5ppm and catalyst loading = 0.3g). The as developed photocatalyst also portrays good recyclability and stability as it showed consistent degradation over 5 cycles. The process followed a pseudo-first-order reaction. Photodegradation of diclofenac also resulted in ten intermediates via various processes such as oxidative displacements, hydroxylation, decarboxylation and cyclization as identified using LCMS-MS analysis.